2004
DOI: 10.1114/b:abme.0000042231.59230.72
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic, Three-Dimensional Deformation of Single Attached Cells Under Compression

Abstract: Abstract-Quantifying three-dimensional deformation of cells under mechanical load is relevant when studying cell deformation in relation to cellular functioning. Because most cells are anchorage dependent for normal functioning, it is desired to study cells in their attached configuration. This study reports new threedimensional morphometric measurements of cell deformation during stepwise compression experiments with a recently developed cell loading device. The device allows global, unconfined compression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…The increased resistance of spread cells to compression results from the stretching of dominant contractile SF bundles. This mechanism is supported by the experimental observations of Peeters et al (2004) for polarised cell geometries, where it is reported that long actin fibres restrict deformation of the cell and nucleus in the direction perpendicular to the dominant fibre orientation. This observation underlines the fully predictive nature of our modelling framework which provides an insightful link between cell geometry, SF distribution and response to mechanical stimuli.…”
Section: Discussionsupporting
confidence: 73%
“…The increased resistance of spread cells to compression results from the stretching of dominant contractile SF bundles. This mechanism is supported by the experimental observations of Peeters et al (2004) for polarised cell geometries, where it is reported that long actin fibres restrict deformation of the cell and nucleus in the direction perpendicular to the dominant fibre orientation. This observation underlines the fully predictive nature of our modelling framework which provides an insightful link between cell geometry, SF distribution and response to mechanical stimuli.…”
Section: Discussionsupporting
confidence: 73%
“…This metric, obtained from biphasic analysis, can be an indicator of cell-to-cell signalling. More common cellular deformation metrics are calculated by first finding the mass moment inertia of each cell and then finding the eigenvalues of this tensor, which represent the principal moments of inertia [57]. These eigenvalues are processed to calculate axis lengths of the inertial ellipsoid, which in turn provide a shape factor from their ratio [51].…”
Section: Post-processingmentioning
confidence: 99%
“…Nonetheless, evidence for this class of pressure ulcers in animal models dates back to the early 1980s. 7,12,13,34,50,53,55 During prolonged tissue loading two different mechanisms of tissue damage have been identified. One mechanism is vascular, in which tissue compression occludes blood vessels in the affected region causing ischemia.…”
Section: Introductionmentioning
confidence: 99%